1999
DOI: 10.1136/hrt.81.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte expression of tissue factor and adhesion molecules: the link with accelerated coronary artery disease in patients with chronic renal failure

Abstract: Conclusion-This study has demonstrated a hypercoagulable state in patients with CRF. This was especially pronounced in the dialysis patients. These findings provide a possible explanation for the increased cardiovascular and cerebrovascular morbidity and mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
4
21
0
1
Order By: Relevance
“…Al-Saady et al showed a hypercoagulable state in patients with chronic renal failure as a contributing factor for the increased cardiovascular and cerebrovascular event rate [16]. Consistent with with the presentresults, Kappelmayer et al…”
Section: Discussionsupporting
confidence: 92%
“…Al-Saady et al showed a hypercoagulable state in patients with chronic renal failure as a contributing factor for the increased cardiovascular and cerebrovascular event rate [16]. Consistent with with the presentresults, Kappelmayer et al…”
Section: Discussionsupporting
confidence: 92%
“…3 We demonstrated previously that monocytes of HIV-1-infected patients express high levels of the procoagulant TF and that TF expression is related to viremia and to plasma levels of both sCD14 and D-dimer products of fibrinolysis. 29 TF can initiate the extrinsic clotting pathway, [47][48][49] potentially linking monocyte activation to coagulation and thrombosis in HIV-1 disease.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate inflammation can protect the body against viruses and other unfavorable factors (Keller et al, 2011), but excessive levels of inflammation are associated with increasing severity of CKD in human patients (Al-Saady et al, 1999;Oberg et al, 2004). We speculated that renal impairment in laying hens resulted from an increase in inflammation.…”
Section: Discussionmentioning
confidence: 99%